Tandem Nickel-Catalyzed Dimerization/(4+2) Cycloaddition of Terminal Alkynes with Four-Membered Ring Ketones - Barday, Manuel; Nicolas, Eva; Higginson, Bradley; Delmotte, François; Appelmans, Martin; Aïssa, Christophe (Synthesis, 2021)
Controlling the behavior of terminal alkynes in metal-catalyzed intermolecular tandem reactions is a formidable challenge despite the potential advantage offered by these strategies in modern synthesis. Herein, we describe that a nickel catalyst enables a tandem process involving the rapid dimerization of terminal alkynes into 1,3-enynes and the cycloaddition of these intermediates with an azetidinone, an oxetanone or benzocyclobutenones. Significantly, the slow or sequential addition of reagents and catalysts is not required to orchestrate their reactivity. These results are in stark contrast with previous cycloadditions of terminal alkynes with strained four-membered ring substrates, which previously led to oligomerization or cyclotrimerization, except in the case of tert-butylacetylene.
Keywords: carbon–carbon bond activation; nickel; catalysis; azetidinone; oxetanone; benzocyclobutenones; tandem